Super Premium Security Prices and Optimal Corporate Financing Decisions: Discussion - Hamada, Robert S. (Journal of Finance, 1976)
Robert S. Hamada, Super Premium Security Prices and Optimal Corporate Financing Decisions: Discussion, The Journal of Finance, Vol. 31, No. 2, Papers and Proceedings of the Thirty-Fourth Annual Meeting of the American Finance Association Dallas, Texas December 28-30, 1975 (May, 1976), pp. 543-546